Pemberdayaan Masyarakat Khususnya Kaum Perempuan Melalui Budidaya Dan Pengolahan Daun Kelor di Desa Salo Timur - Fandi Bagus Wurtantomo; Anggraeny Glory Roito Purba (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Salo Timur Village in Salo Sub-district, Kampar Regency, Riau Province is one of the villages where the community has a low income or the majority of the community is still in a poor condition, especially women. Women are often marginalized, they face challenges in their role and participation in village development, and they are also faced with difficulties in increasing family income and welfare. One of the things done to overcome the problems of the community, especially women, is through community empowerment activities by utilizing the potential of abundant natural resources, including the existence of moringa trees that thrive in the vicinity. The empowerment activities carried out are through cultivation and processing of moringa leaves. The learning approach used in this training is the Andragogy approach with lecture, discussion and practicum methods. The implementation of community empowerment activities in Salo Timur Village was carried out on June 2, 2022 through moringa cultivation and processing activities. The results of this activity are increasing the role of women in village development, through increasing their ability to cultivate and process moringa leaves so that they can be utilized as a source of livelihood.